Hemodynamics Change and Clinical Efficacy on Cervical Spondylosis of Vertebral Artery Type Treated by Hot Compress Therapy with Medicinal Salt Pillow - Li CHEN; Lijun YAO; Li ZHAO; Chunqiao FU; Xiaoyu XU (康复学报)
Objective:To investigate the effect of hot compress therapy with medicinal salt pillow on cervical spondylosis of vertebral artery type, and to observe the effects on symptoms, cervical function and clinical effect of patients.Methods:A total of 80 patients with cervical spondylosis of vertebral artery type were randomly divided into observation group and control group according to the proportion of 1∶1 used by SPSS 17.0 software random sequence generation module, with 40 cases in each group. The patients in observation group were treated by hot compress therapy with medicinal salt pillow filled with Daqing salt as a heat conductor, and the patients in control group were treated by wax therapy and cervical traction. After 4 weeks of treatment, transcranial doppler ultrasound (TCD) was used to compare the blood flow velocity and asymmetry, and pulsatile index (PI) of the bilateral vertebro-basilar artery before and after treatment in the two groups. The cervical vertigo symptom and function assessment scale (ESCV) was used to evaluate the degree of symptoms and function of patients, and the clinical efficacy was evaluated according to the therapeutic standard of traditional Chinese medicine.Results:1) There were no statistical differences between the two groups before treatment for the indicators of blood flow velocity and asymmetry, PI of the bilateral vertebro-basilar artery and the score of ESCV(P> 0.05). 2) After four weeks treatment, the mean of peak systolic blood flow velocity[(LVA+RVA) VP/2]and the mean of end diastolic blood flow velocity[(LVA+RVA) Vd/2]of the bilateral vertebro-basilar artery in both groups with slow blood flow velocity were significantly higher than those before treatment (P< 0.05). For the patients in both groups with rapid blood flow velocity, the (LVA+RVA) Vp/2 was obviously lower than that before treatment (P< 0.05), and the decrease of (LVA+RVA) Vd/2 was not as significant as that of (LVA+RVA) Vp/2. Compared with the control group, the improvement of (LVA+RVA) Vp/2 in the observation group with slow blood flow velocity after treatment was more significant (P< 0.05). 3) The PI was reduced after treatment in the two groups, and the reduction in observation group with slow blood flow velocity was superior to that in the control group after treatment (P< 0.05). 4) The asymmetry of blood flow velocity showed that the difference of peak systolic blood flow velocity of bilateral vertebro-basilar artery[|LVA-RVA|Vp]in the observation group was dropped significantly after treatment (P< 0.05). The ESCV scores were both improved after treatment for the two groups (P< 0.05), with the scores of observation group (23.13±3.15) higher than the control group (21.73±3.39), however, the difference was not statistically significant (P> 0.05). There was no statistically significant difference of clinical efficacy between the two groups (P> 0.05), and no adverse reactions were observed in either groups.Conclusion:The effect of hot compress therapy with medicinal pillow filled with salt can significantly improve the blood flow of bilateral vertebro-basilar artery, effectively relieve the symptoms of cervical spondylosis of vertebral artery type and improve the function of cervical vertebra.